PEMODELAN KOPERASI WANITA DALAM PENINGKATAN KESEJAHTERAAN PEREMPUAN DI KABUPATEN BLITAR - Nurul - Farida; Suprianto - - (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2018)
Life welfare is the hope of every society and society welfare is the goal of the goverment to create a fair society, properous and safe is required some kind progam of the activities community. This research is to contribute the modeling of women cooperation in improving of welfare. Women cooperation is one of groups community that have purpose to increase women ability to increase his life by activities what he did. From the result of the reseach can be conclusion that the affect the level of welfare is happiness, they will feel happy when fulfilled necessities of her life, education wich is can reach the cost of education and quality of life, wich is recognition and public trust about her ability so they can be more quality theirself.